A severe case of the bladder inversion treated by total cystectomy and hysterectomy with ileal conduit - Taro Akai; Naoki Kawamorita; Tetsuro Shiraiwa; Mahoro Watanabe; Tomonori Sato; Takuma Sato; Emi Yokoyama; Masumi Ishibashi; Zen Watanabe; Akihiro Ito (IJU Case Reports)
Introduction Female pelvic organ prolapse (POP) is considered a borderline disease between urology and gynecology and is treated by reconstructive surgery, which restores the organs to their original positions. Case presentation An 82‐year‐old woman with bladder and uterine prolapse at POP‐Q Stage IV was treated with an indwelling catheter for voiding dysfunction. Eventually, the catheter has been often spontaneously removed when pelvic organ prolapse occurs, resulting in a diagnosis of bladder inversion. Because of bladder inversion and low bladder capacity at the time of bladder retraction, the patient underwent total cystectomy, combined with total hysterectomy, colpopexy, and posterior colporraphy, and ileal conduit. Conclusion The cases of complete bladder and uterine prolapse combined with bladder inversion, total hysterectomy, colpopexy, posterior colporraphy, and ileal conduit were performed safely. Considering urinary function, surgery without organ preservation with urinary diversion may be an option.